Business negotiations: communication in the bargaining process - Põlajeva, Tatjana (Journal of Business Economics and Management, 2017)
Kęstutis Peleckis. Business negotiations: communication in the bargaining process: monograph. North Charleston, USA: createspace, 2016. 224 p.